Analysis of Murabahah Financing for Customers Who Die Before the Maturity: Study of KBSU Tikung Lamongan - Buana, Miftahal Anjarsabda Wira; ZA, Moh. Ah. Subhan; Jannah, Nur (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Financing customers who die before maturity but still have financing is one of the situations that occur in KBSU Lamongan, savings from depositors used for financing are naturally the responsibility of the bank in running its business. Based on the background above, the researcher is interested in raising the title